Nucleoside-based diarylethene photoswitches and their facile incorporation into photoswitchable DNA - Cahová, Hana; Jäschke, Andres (Angewandte Chemie. International edition, 2013)
Come into the light: Pyrimidine nucleosides were found to undergo fast and reversible ring closure upon irradiation with light when covalently attached to 2-[2-methyl-5-phenylthien-3-yl]cyclopent-1-ene (see scheme). Synthesis using an aqueous-phase Suzuki-Miyaura cross-coupling allows for one-step conversion of iodo-modified oligonucleotides into fully reversible DNA photoswitches.
Gesehen am 05.02.2021